"I'm in Between": Cultural Identities of Chinese Youth in Canada. Issue 2 (April 2020) - Fang, Lin; Huang, Yu-Te
This constructivist grounded theory study unpacks how Chinese youth in Canada navigate and negotiate their cultural identities. Participants aged 16 to 24 years ( N = 22) were invited to provide a biographic account of where they were born and raised, the social contexts they interacted with, and how they grappled with their cultural identities growing up. Despite noting the differences between Chinese and Canadian cultures, participants found the concepts of culture elusive and questioned the categorical notion of culture. They indicated their cultural identity as being "in-between, " and their identity development as an ongoing, nonlinear process, involving a constant exchange between them and their environments. Study results highlight the fluid and nonstatic nature of cultural identity development in the context of immigration.